Foreigners and Narcotics Crimes: How Indonesian Laws Determine the Supervision Mechanism? - Kartika, I Gusti Ayu; Setiabudhi, I Ketut Rai; Winarsi, Sri (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 8 No 3 (2019), 2019)
Oversight of foreigners becomes very important in line with the increase in international crime, one of which is a narcotics crime. Through technological developments, the spread of narcotics has reached almost all regions in Indonesia. The state does not want its territory to have people involved in narcotics crimes. The main objective of the supervision of foreigners is to protect the community and the sovereignty of the State. The aim of the study to analyze who has authorized to conduct surveillance of foreigners related to narcotic crimes. This research is a normative legal research using the legislation approach and concept approach. The results of the research are: The authority to supervise foreigners related to narcotics criminal acts based on the Immigration Act is carried out by the Minister by forming a team consisting of relevant government agencies or agencies both at the central and regional levels. The institution is the Immigration Agency and is also carried out by the National Narcotics Agency which coordinates with the Police. Furthermore, based on the Law on narcotics that is authorized to conduct surveillance of Narcotics crime as regulated under the provisions of Article 61 paragraph (1) is the Government. The government supervises all activities related to Narcotics.. Oversight of Foreigners related to narcotics crime, is not only done when they enter, but also while they are in the Territory of Indonesia, including their activities. Immigration Supervision covers the enforcement of immigration law, both administrative and Immigration.